In-vitro Analysis of Titanium Cellular Structures Fabricated by Direct Metal Laser Sintering. (2020) - Jaivignesh, M.; Suresh Babu, A.; Arumaikkannu, G.
Abstract: In vitro analysis of implants helps in determining biocompatibility, growth of cell and reaction of material to fluids of body. Mandibular implant is considered for the application of cellular structures in this work and Titanium alloy (Ti64) being a biomaterial, is selected for the study. The Ti64 cellular structures were designed with 10mm x 10mm x 3mm size, with pore size 1 mm and inter-pore distance 1.6 mm and were fabricated using Direct Metal Laser Sintering (DMLS) process. MG-63 Osteosarcoma cells were utilized for the analysis to mimic the bone cells associated with the mandibular implant. The cellular structure's biocompatibility analysis was performed after a particular time interval of 12 th hour, 24 th hour and 36 th hour (through measurement of the growing cells). On an average, the control samples showed 100 % viability whereas treatment samples showed nearly 139.83 % viability i.e there is an improvement in cell growth with respect to Ti64 cellular structures. Thus the direct metal laser sintered Ti64 cellular structure is suitable for mandibular implant application